A modified uniformly distributed heat source method for predicting braking temperature of railway brake disc. Issue 2 (4th March 2022) - Yuan, Zewang; Tian, Chun; Wu, Mengling; Wang, Guozhuang
ABSTRACT: The current numerical method can only obtain the average temperature of the railway brake disc, which greatly reduces the predicting accuracy. Based on the uniformly distributed heat source method (UDHS Method), a more accurate and efficient method was proposed to predict the braking temperature by using a cosine function. This numerical method is valid as its results are in good agreement with the measurements from the full-scale rig test. After modification, the errors of the predicted maximum temperature are decreased from 5.73–6.72% to 3.47–5.07% at 40–100 km/h, and the temperature curves oscillate with a cosine form whose frequency is perfectly match with the curves from the thermal mechanical coupling method (TMC Method). The computational time of TMC Method is 74.19–665.61 times as much as that of UDHS Method, while the ratio of the modified method is reduced to 2.76–12.95 times.